2000
DOI: 10.1054/bjoc.1999.1004
|View full text |Cite
|
Sign up to set email alerts
|

Continuous low dose Thalidomide: a phase II study in advanced melanoma, renal cell, ovarian and breast cancer

Abstract: To grow and metastasize, solid tumours must develop their own blood supply by neo-angiogenesis. Thalidomide inhibits the processing of mRNA encoding peptide molecules including tumour necrosis factor-alpha (TNF-α) and the angiogenic factor vascular endothelial growth factor (VEGF). This study investigated the use of continuous low dose Thalidomide in patients with a variety of advanced malignancies. Sixty-six patients (37 women and 29 men; median age, 48 years; range 33–62 years) with advanced measurable cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
127
0
5

Year Published

2000
2000
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 316 publications
(137 citation statements)
references
References 35 publications
5
127
0
5
Order By: Relevance
“…Bertolini showed reductions in VEGF and bFGF levels which corresponded to clinical response in patients with multiple myeloma treated with thalidomide [13]. However, in a phase II study of low dose thalidomide (100 mg/day) to treat 66 patients with advanced renal cell carcinoma, melanoma, ovarian cancer, or breast cancer, no relationship was seen between serum VEGF or bFGF levels and treatment or response [36]. In an effort to better understand the role of angiogenesis in endometrial cancer, serum and plasma levels of VEGF and bFGF were measured prior to and after 4-6 weeks of thalidomide.…”
Section: Discussionmentioning
confidence: 99%
“…Bertolini showed reductions in VEGF and bFGF levels which corresponded to clinical response in patients with multiple myeloma treated with thalidomide [13]. However, in a phase II study of low dose thalidomide (100 mg/day) to treat 66 patients with advanced renal cell carcinoma, melanoma, ovarian cancer, or breast cancer, no relationship was seen between serum VEGF or bFGF levels and treatment or response [36]. In an effort to better understand the role of angiogenesis in endometrial cancer, serum and plasma levels of VEGF and bFGF were measured prior to and after 4-6 weeks of thalidomide.…”
Section: Discussionmentioning
confidence: 99%
“…13 At the clinical level, a Phase I study of the natural sterol squalamine, 32 and Phase II studies of the T cell-and NK cell-regulating factor IL-12, 33 carboxyamidotriazole (a factor inhibiting transmembrane calcium influx in vascular endothelial cells) 34 and thalidomide (known as a phocomeliacausing drug and having powerful antiangiogenic activity) 35 have been reported. It has been confirmed that these molecular-targeting agents have tumor growth-suppressive activity and antiangiogenic activity in subcutaneous tumor models.…”
Section: Discussionmentioning
confidence: 99%
“…13 Tolerability to the 4 drugs at the Phase I and II clinical trial stages has been confirmed. [32][33][34][35] Single-agent IL-12 has a low response rate in recurrent ovarian cancer patients, 33 however, and single-agent carboxyamidotriazole has no tumor-regression activity, only suppressing tumor progression. 34 Because moleculartargeting therapy alone is limited to the tumor-regression effect, it is clinically used in combination with conventional anticancer drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Eisen et al used low-dose thalidomide as an anti-angiogenic agent in patients with advanced melanoma, ovarian and breast cancer. 27 Thalidomide has a direct effect on the cancer tissue itself through its anti-angiogenic properties. Tumour size reduction in implanted human oesophageal cancer in an animal model has been shown.…”
Section: Discussionmentioning
confidence: 99%